1994
DOI: 10.1093/nar/22.11.1988
|View full text |Cite
|
Sign up to set email alerts
|

DifferentTrypanosoma bruceiguide RNA molecules associate with an identical complement of mitochondrial proteinsin vitro

Abstract: RNA editing is a mitochondrial transcript maturation process which evolved in kinetoplastid protozoa. It entails the insertion and deletion of exclusively uridine nucleotides directed by gRNAs into pre-mRNAs. Other participating components are not currently known. The aim of this study was to identify mitochondrial proteins that are in direct physical contact with gRNAs thereby possibly involved in the editing reaction. At low monovalent cation concentration (30 mM KCl) 8 polypeptides with apparent molecular w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
48
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 34 publications
8
48
1
Order By: Relevance
“…Despite the differences in the molecular mass estimation and also some differences in the experimental conditions, the identified characteristics of that cross-link were very similar with one obvious difference: Leegwater et al (15) reported a dependence on a long U-tail on the gRNAs whereas Köller et al (16) found cross-linking even with a tail-less gRNA substrate. There is no apparent explanation for this difference but all other features support the interpretation that this cross-link is based on the interaction of gRNAs to the same protein or the same set of proteins.…”
mentioning
confidence: 83%
See 4 more Smart Citations
“…Despite the differences in the molecular mass estimation and also some differences in the experimental conditions, the identified characteristics of that cross-link were very similar with one obvious difference: Leegwater et al (15) reported a dependence on a long U-tail on the gRNAs whereas Köller et al (16) found cross-linking even with a tail-less gRNA substrate. There is no apparent explanation for this difference but all other features support the interpretation that this cross-link is based on the interaction of gRNAs to the same protein or the same set of proteins.…”
mentioning
confidence: 83%
“…Extracts were cleared from insoluble material by centrifugation at 16,000 ϫ g for 5 min at 4°C and protein concentrations were determined by dye-binding using bovine plasma ␥-globulin as a standard (26). The purification of gBP21 was followed by monitoring the binding activity to T. brucei gRNA gA6-14 (16). Cleared extracts were precipitated with ammonium sulfate at 4°C and the protein was enriched in the 50 -60% (w/v) saturation fraction.…”
Section: Cell Growth Preparation Of Nucleic Acids and Mitochondrialmentioning
confidence: 99%
See 3 more Smart Citations